Microstructural characterisation of GaMnN ferromagnetic semiconductors grown on (001) oriented GaAs substrates by plasma assisted molecular beam epitaxy - Han, Yisong (2006)
GaMnN layers grown by plasma assisted molecular beam epitaxy (PAMBE) as a function of Ga/N ratio, Mn flux and growth temperature are assessed using a variety of structural characterisation techniques. At 680 C, the Ga/N ratio is found to have a dominant impact on the zinc-blende GaMnN epilayer growth rate and the resultant composition, morphology and microstructure. A maximum growth rate and an optimised microstructure are associated with growth under slightly Ga-rich conditions. A reduced growth rate and enhanced Mn incorporation are associated with growth under slightly N-rich conditions. Increasing Mn flux under N-rich conditions is considered to lead to a build up of a Mn surfactant layer during the early stages of growth and to a transition from zinc-blende single phase growth to zinc-blende/wurtzite mixed phase growth. Further, under Ga-rich conditions at low temperature, GaMnN films adopt a tilted growth mode, with close packed planes for both hexagonal and cubic phases being tilted roughly parallel to the growth surface, and this way of modified growth is also accompanied by improved Mn incorporation which is not commonly found for samples grown under Ga-rich conditions at elevated temperature. In addition, alpha-MnAs inclusions and voids extending into the GaAs buffer layer were identified in all samples, but are considered not to have a detrimental effect on layer electrical and magnetic properties.